Return of Sinamot Money from the Perspective of Al'adatu Muhakkamah (Analysis of the Decision of the Padangsidimpuan City Religious Court Number 129/Pdt.G/2015/PA.Psk) - Baskoro, Bayu; Fatimah, Fatimah; Khalid, Khalid (Universitas Islam Sultan Agung, 2024)
This paper is a study on the return of sinamot money in the decision of the Religious Court by examining based on the perspective of the fiqh rule Al'adatu Muhakkamah, which examines the reality that the lawsuit for the return of sinamot money submitted to the Padangsidimpuan City Religious Court, by the Panel of Judges was partially returned, with considerations that contain justice, certainty and legal benefits and cannot be separated from the consideration that custom is the law